Effects of Liquid-to-Solid Ratio and Reaction Time on Dilute Sulfuric Acid Pretreatment of Achnatherum splendens - Ren, J.; Tao, L.; Ni, T.R. (Asian Journal of Chemistry, 2015)
In sulfuric acid pretreatment of Achnatherum splendens, the ground biomass was pretreated by 0.5-3 % (w/v) sulfuric acid with 8:1-20:1 (v/w) of liquid-to-solid ratio at 100 °C for 1-4 h. Increasing sulfuric acid concentration, liquid-to-solid ratio and reaction time had significant effects on hemicellulose solubilization. Increasing the sulfuric acid concentration, liquid-to-solid ratio and reaction time caused significant decrease in hemicellulose and significant increase in formation of cellulose and lignin. The optimum treatment conditions of sulfuric acid pretreatment for Achnatherum splendens were 2 % (w/v) sulfuric acid, 15:1(v/w) of liquid-to-solid ratio, 3 h of reaction time and temperature 100 °C. Under these conditions, 92.57 % hemicellulose was solubilized and the content of cellulose in pretreated solids increased to 66.79 %. This study can serve as a step towards the optimization of pretreatment of Achnatherum splendens.